SEDIMENTOLOGY AND BIOSTRATIGRAPHY OF AN UPPER TRIASSIC CARBONATE SUCCESSION OF TRIPOLITZA PLATFORM IN MARI AREA, PARNON MOUNTAIN, SE PELOPONNESUS, GREECE - Kati, M.; Zambetakis-Lekkas, A.; Skourtsos, E. (Bulletin of the Geological Society of Greece, 2007)
The Upper Triassic succession in the base of Tripolitza carbonate platform, in the Mari area of the Parnon Mt. in SE Peloponnesus, mostly consists of dolomites and to a lesser extent ofcalcitic dolomites. A detailed fades analysis and biostratigraphical study revealed that during Norian — Rhaetian times inter-supratidal and subtidal (shallow lagoonal) fades presenting cyclic development were deposited in the inner platform, similar to those that were formed in most of the Alpine platforms of the southern margin of the Tethys during the same time period. Diagenetic considerations further indicate that this shallow marine carbonate sedimentation was interrupted by subaerial exposure intervals and subsequent early lithification of the recently deposited sediments. The extensive and, mainly, early dolomitization and recrystallization, the presence of meteoric-vadose cements and specifically the repeated appearance of dolocrete horizons in the upper parts of many peritidal cycles, clearly show periodic subaerial exposure of the sediments, as well as the prevalence of semi-arid conditions in the area.